O professor, de Cristovão Tezza: uma paródia fáustica - Fernandes, Maria Aparecida (2017)
The dissertation proposes a reading of Cristovão Tezza’s novel O professor [The Professor] as a parody based on the Faust theme. According to critics, that romanesque prose is considered one of the most ambitious book written by Tezza. Initially the research presents an overview of Tezza’s writings: his novels, reviews, essays and academic production, corroborating the author’s relevance as a major name in contemporary Brazilian literature. The work then delineates the novel’s main aspects, tracing the origin of the Faust myth and pointing to its importance in literature up to the present time. Faust, a character who sought control over man and nature, projects a shadow on the novel’s narrator and protagonist, Prof. Heliseu, reminding us that a ‘faustic’ ideology is more than ever in progress. Consequently, the reading of the novel must find out an opening key to the convincing monologic world created by the narrator’s authoritative speech. The key is given by Bakhtin’s theory of language which leads inescapably to the questioning of the narrator’s unilateral word and even challenges the very limits of language. The research is made through the investigation of various intertextual games of language and their parody usages. Games which intertwine different types of discourse in the novel O professor [The Professor]: poetry, historiography, essay, legend. The dissertation also focus on the dialogic relation between aspects of the ancient Menippean satire and the parody. The analysis follows a Bakhtinian perspective on the mingling of serious and comic literary genres taking into consideration the categories proposed by the Russian phylosopher. As a conclusion it could be stated that the presence of the grotesque creates a carnivalistic atmosphere which pervades the whole narrative